Redox chemistry, solubility and hydrolysis of Re in reducing aquatic systems. Thermodynamic description and comparison with Tc. (September 2021) - Duckworth, S.; Gaona, X.; Castaño, D.; Park, S.; Altmaier, M.; Geckeis, H.
Abstract: The aqueous solution chemistry of rhenium was investigated in acidic to hyperalkaline reducing systems buffered by Sn(II) and Na2 S2 O4 . Oversaturation experiments with [NaReO4 ]0  = 10 −3  M were used to evaluate the redox chemistry of Re(VII)/Re(IV), whereas the solubility and hydrolysis of Re(IV) were investigated in a series of undersaturation experiments with ReO2 (s). The predominance of Re(IV) is predicted under the very reducing conditions defined by Sn(II) and Na2 S2 O4 (at pe + pHm  ≈ 1–5) (with pHm  = –log [H + ] and pe = – log a e– ), according to thermodynamic calculations represented as Pourbaix diagrams. In contrast to Tc(VII), Re(VII) shows recalcitrance to the reduction in Sn(II) systems except at pHm  ≈ 1 and ≈12.8. As previously reported in the literature, the reduction of Re(VII) observed at pHm  ≈ 1 is expectedly triggered by the co-precipitation of Re(IV) with the SnO2 (s) solid phase forming through the in-situ oxidation of Sn(II). The faster reduction kinetics reported for Tc(VII) can be partly explained by the more positive standard potential ( E °) of the couple TcO4 − /TcO2 (s) compared to that of ReO4 − /ReO2 (s), which results in a greater driving force for the reduction of TcO4 − under the same conditions. The solubility of ReO2 (s) remains low (≈10 −6  M) and pH-independent within 1 ≤ pHm  ≤ 10, but increases with a slope of +1 (log [Re] vs. pHm ) above pHm  ≈ 10. A combination of solid phase characterization, solubility data determined in this work and reported in the literature are considered to derive chemical and thermodynamic models including the solubility reactions ReO2 (s) + H2 O(l) ⇔ ReO(OH)2 (aq) and ReO2 (s) + 2H2 O(l) ⇔ ReO(OH)3 –  + H + . Thermodynamic data determined in this work for the hydrolysis of Re(IV) show a good agreement with thermodynamic data reported for Tc(IV), and represent a significant improvement with respect to previous studies available on the Re(IV) system. Experimental evidence obtained in this work support the chemical analogy of Re and Tc in the +IV oxidation state, which is rationalized by the very similar ionic radii of both metal ions. Notwithstanding, these elements show a remarkably different redox chemistry, both in terms of kinetics and thermodynamic stability. The use of Re as an inactive analogue of Tc in systems involving redox transformations must therefore be considered with precaution. Highlights: Redox and solubility of Re(VII)/Re(IV) investigated in reducing systems. Recalcitrant to reduction of Re(VII) observed within 3 ≤ pH ≤ 12. Significant differences observed between Re(VII) and Tc(VII) reduction kinetics. Thermodynamic model derived for solubility and hydrolysis of Re(IV). Similar hydrolysis behavior observed for Re(IV) and Tc(IV).